230 A dog with a bone (marrow biopsy). Issue 12 (14th November 2019) - Li, Vivien; Kapoor, Mahima; Lunn, Michael; Cwynarski, Kate; Carr, Aisling
Abstract : A 71-year-old woman presented with severe painful meningoradiculoneuritis progressing over 6 weeks. She had localised breast cancer treated 13 years prior. Differentials included a vasculitic or infiltrative process. Neurophysiology showed a patchy, predominantly proximal axonal process with widespread active denervation. MRI revealed asymmetrical enhancement of the brachial plexus, left S1 and multiple cranial nerves. CSFs were lymphocytic (normal T-cells predominant), with elevated protein and negative cytology. FDG-PET was negative for malignancy. BMAT showed no evidence of a lymphoproliferative condition. Left sural nerve biopsy was non-diagnostic. Right brachial plexus biopsy showed mixed T-/B-cell endoneurial inflammation not fulfilling criteria for vasculitis. She was stabilised with high-dose steroids and cyclophosphamide, followed by mycophenolate for inflammatory myeloradiculoneuritis. However, symptoms recurred when prednisolone was weaned. Although T-cell receptor gene analysis from the initial BMAT demonstrated clonal rearrangements, it was only when the same clones were identified on two repeat BMATs and CSF that T-cell neurolymphomatosis was diagnosed. Poor performance status precluded chemotherapy. She continued on prednisolone and cyclosporine for 3.5 years, before dying of sepsis. T-cell neurolymphomatosis is exceedingly rare. Clonality assessment can increase yield when other investigations including histology are non-diagnostic. This case highlights the value of repeated investigations when clinical suspicion is high.